2014
DOI: 10.1007/s11920-014-0500-x
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Sleep and Emotion Regulation: Conceptual Framework Empirical Evidence and Future Directions

Abstract: Emotions are biologically-based responses that help an organism meet challenges and opportunities, and involve changes in subjective experience, behavior, and physiology. Emotions arise when something important to us is at stake. Although many factors have been associated with healthy emotional regulation, the role of sleep in this process has been largely ignored. Recent studies, however, have begun to delineate how sleep critically affects emotional functioning. Nighttime sleep affects daytime mood, emotiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
160
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(171 citation statements)
references
References 72 publications
10
160
1
Order By: Relevance
“…Surprisingly, we know little about the pathways by which poor sleep begets depression symptoms. This study was a first step in this direction, examining whether sleep problems might be associated with depression because of disturbance to emotion regulatory mechanisms (Gruber & Cassoff, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, we know little about the pathways by which poor sleep begets depression symptoms. This study was a first step in this direction, examining whether sleep problems might be associated with depression because of disturbance to emotion regulatory mechanisms (Gruber & Cassoff, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, sleep-deprived participants have shown reduced functional connectivity in systems associated with cognitive control of emotional response (Yoo et al, 2007; but see Minkel et al, 2012 for additional discussion). Furthermore, disordered sleep impairs executive function systems, which have direct consequences for the ability to regulate emotions (for a review, see Gruber & Cassoff, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…For example, headaches, back/joint pain, depression, and anxiety, to name a few, have all been shown to vary across the menstrual cycle (Mortola et al 1990;Kiesner and Pastore 2010) and are also associated with sleep difficulties. Past research has shown that both affective symptoms and pain conditions (e.g., headaches) are commonly associated with sleep problems (Finan et al 2013;Gruber and Cassoff 2014). Thus, to understand the association between the menstrual cycle and sleep problems, it is important to consider psychological and physical factors that may be associated with both menstrual cycle phase and disrupted sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of sleep, specifically sleep deprivation, on emotions and moods has been well documented in the experimental literature, but despite acknowledgement in the literature of a bidirectional relationship between emotions and sleep, the mechanisms through which emotions impact sleep has received less attention (6). Maladaptive strategies for managing affect are associated with difficulties in emotion regulation, which in turn may increase the risk for poor sleep quality (6–8).…”
Section: Introductionmentioning
confidence: 99%
“…Maladaptive strategies for managing affect are associated with difficulties in emotion regulation, which in turn may increase the risk for poor sleep quality (6–8). In a recent time-lagged analysis using daily diary data, Kouros and El-Sheikh (2015) examined bidirectional associations between sleep and mood in a community sample of 142 elementary school children (9).…”
Section: Introductionmentioning
confidence: 99%